Analyzing the Relationship between Risk Management Strategies and Supply Chain - Nureen, Puteri (International Journal of Supply Chain and Logistics, 2024)
Purpose: The purpose of this article examined how different risk management strategies affect supply chain resilience in Malaysia. It aims to identify effective strategies, such as supplier diversification and digitalization, that help Malaysian companies mitigate disruptions. The findings offer insights to enhance operational continuity and adaptability within Malaysia's unique risk environment. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that effective risk management strategies, like supplier diversification and real-time monitoring, significantly enhance supply chain resilience in Malaysia. Companies adopting these strategies experienced fewer disruptions and quicker recovery times. However, challenges such as high costs and limited technology access still hinder broader adoption among smaller firms. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV), contingency theory & high reliability theory (HRT) may be used to anchor future studies on the relationship between risk management strategies and supply chain resilience in Malaysia. Practically, companies should implement risk management strategies that are tailored to their specific supply chain contexts and risks. At the policy level, governments and industry bodies should support the adoption of resilience-enhancing technologies by offering financial incentives or subsidies, particularly for small- and medium-sized enterprises.